2004
DOI: 10.1128/iai.72.9.5181-5192.2004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Targets Adherens Junction Regulatory Proteins and Results in Increased Rates of Migration in Human Gastric Epithelial Cells

Abstract: The human gastric pathogen Helicobacter pylori attaches to antral epithelial cells in vivo. Cultured human antral epithelial cells, AGS and NCI-N87 cell lines, were grown in the absence or presence of H. pylori and compared with respect to gene transcript levels, protein expression, organization of the actin cytoskeleton, and the regulation of cell migration. The Clontech Neurobiology array detected differentially expressed transcripts, while Western blots were used to investigate related changes in protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…However, it is becoming clear that H. pylori can also have more-direct effects on the AJ. Indeed, in vitro H. pylori can rapidly disrupt the integrity of the AJ without affecting E-cadherin and ␤-catenin expression (10,45). Our results also indicate that H. pylori disrupts AJs at an intracellular level via activation of the host cell protease calpain.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, it is becoming clear that H. pylori can also have more-direct effects on the AJ. Indeed, in vitro H. pylori can rapidly disrupt the integrity of the AJ without affecting E-cadherin and ␤-catenin expression (10,45). Our results also indicate that H. pylori disrupts AJs at an intracellular level via activation of the host cell protease calpain.…”
Section: Discussionsupporting
confidence: 58%
“…␤-Catenin is aberrantly activated in gastric cancer precursor lesions (40), suggesting that AJ modifications precede adenocarcinoma development. Studies using a gerbil-adapted strain of H. pylori in an in vivo model of disease have shown that ␤-catenin activation plays a role in gastric tumorigenesis (14), and AJ disruption has been linked to increased cell migration (10,45) and cellular transdifferentiation from a gastric to an intestinal phenotype in vitro (29). However, despite advances in this area, the mechanisms whereby persistent H. pylori infection alters gastric epithelial AJs remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, normal and gastric cancer cells were infected with H. pylori and differential expression of genes and proteins measured (133). H. pylori infection consistently up-regulated Annexin II, S100A7 and the Rho-GTP protein and significantly altered the location of E-cadherin from plasma membrane to intra-cellular vesicles (133).. Based on the results, the authors suggested that H. pylori infection results in destabilizing epithelial cell adherence via the up-regulation of specific membrane associated proteins such as Annexin II and S100A7, which may play a role in increasing the risk of gastric carcinogenesis (133).…”
Section: A Role Of Anx-ii In Gi Cancersmentioning
confidence: 99%
“…AGS (ATCC CRL-1739 [56]) or NCI-N87 (CRL-5822 [13]) human gastric epithelial cells were cultured according to the ATCC guidelines in Dulbecco's modified Eagle's medium (DMEM). To assay cytokine and chemokine production, cells were seeded at 2 ϫ 10 5 cells/well in 24-well tissue culture plates and incubated for 24 h. After this time, H. pylori, cultured for 24 h on CHBA, was scraped from a plate and resuspended in sterile DMEM or phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%